System Design Optimization for Product Manufacturing - Yoshimura, Masataka; SpringerLink (Online service) (London : Springer London, 2010)
Product manufacturing is currently one of the most important activities that people perform, as it directly or indirectly affects the daily life and economic well-being of countless people around the world. It is likely to continue to have a profound effect on world economies by providing a large source of employment and, ideally, by creating products that positively affect the lives of numerous people. For manufacturing to be successful in the long run, a broad range of factors must be taken into account when products are designed and developed. Product manufacturing today requires skilful decision-making in scenarios that are more complex and demanding than ever before, and the use of optimal system technologies has become essential. Readers of System Design Optimization for Product Manufacturing will learn about detailed concepts and practical technologies that enable successful product design and manufacture. These concepts and technologies are based on system optimization methodologies that consider a broad range of mechanical, as well as human, factors. System Design Optimization for Product Manufacturing explains the methodologies behind current and future product manufacture. Its detailed explanations of key concepts are relevant not only for product design and manufacture, but also for other business fields. These core concepts and methodologies can be applied to practically any field where informed decision-making is important, and where a range of often conflicting factors must be carefully weighed and considered. System Design Optimization for Product Manufacturing can be used as a fundamental reference book by both engineers and students in the fields of manufacturing, design engineering, and product development.
Progression of Product Manufacturing Technologies -- Evaluative Criteria for Product Manufacturing and Optimization Fundamentals -- Technologies for Product Manufacturing Innovation -- Involvement of People in Product Manufacturing -- Product Manufacturing Support Technologies -- Optimization Technologies for Product Manufacturing -- Decision-making Methods -- Design Optimization for Creativity and Balance.
Keywords: Engineering; Computer aided design; Engineering economy; Machinery; Engineering; Manufacturing, Machines, Tools; Engineering Economics, Organization, Logistics, Marketing; Computer-Aided Engineering (CAD, CAE) and Design